1995
DOI: 10.1093/clinchem/41.12.1710
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin-I is not expressed in fetal and healthy or diseased adult human skeletal muscle tissue

Abstract: Cardiac troponin-I (cTnI) is not found in sera of patients with skeletal muscle disease in the absence of myocardial injury. It is not known, however, whether trace amounts of cTnI are expressed in regenerating human skeletal muscle, as has been observed with creatine kinase MB. Using immunohistochemical and biochemical techniques, we investigated cTnI expression in various human muscle tissues: human heart tissue (n = 5), normal adult skeletal muscle (n = 3), and fetal heart (n = 3) and skeletal muscle (n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0
5

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(92 citation statements)
references
References 0 publications
1
86
0
5
Order By: Relevance
“…23,24 CTnI appears to be more specific than cTnT for myocardial injury. 25 Possible increases in serum cTnT concentration with skeletal muscle trauma may be one disadvantage of cTnT compared to cTnI. 2nd-generation cTnT assays (such as the Elecsys used in this study) are reported to be more specific for myocardial injury than 1st-generation assays.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…23,24 CTnI appears to be more specific than cTnT for myocardial injury. 25 Possible increases in serum cTnT concentration with skeletal muscle trauma may be one disadvantage of cTnT compared to cTnI. 2nd-generation cTnT assays (such as the Elecsys used in this study) are reported to be more specific for myocardial injury than 1st-generation assays.…”
Section: Discussionmentioning
confidence: 76%
“…cTnI has been shown to be a more sensitive and specific marker of myocardial injury. 4,21,[23][24][25] However, some normal dogs may experience slight increases in cTnI, which may cause difficulty in assessing a clinically relevant increase in concentration. 21 Finally, the lack of standardization among the different assays for cTnT and cTnI may be problematic for its widespread clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…4 Among the cardiac troponins, cTnI is more specific than cTnT in detecting myocardial damage because cTnT may be expressed by skeletal muscle in human patients with renal failure and muscular dystrophy. 1,25,[27][28][29][30] In this study, plasma cTnI concentrations were measured using the assay developed for use in people, because no sheep-specific assay is available. cTnI is measured by automated immunoassay, and the difference in amino acid sequence between skeletal and cardiac muscle troponin I has permitted production of antibodies specific for cTnI.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 It is not expressed in skeletal muscle during disease states and is, thus, uniquely cardiac. [14][15][16] The full gene sequence of cTnI in dogs and cats has been determined, and the homology between canine/feline and human cTnI genes is 95 and 96%. 17 As the troponins are purely intracellular proteins, their presence in circulation reflects intracellular content release from cardiomyocytes.…”
Section: Cardiomyocyte Physiologymentioning
confidence: 99%